2023
DOI: 10.3390/nu15122748
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Angiogenic Effects of Natural Compounds in Diet-Associated Hepatic Inflammation

Abstract: Alcoholic liver disease (ALD) and non-alcoholic fatty liver disease (NAFLD) are the most common causes of chronic liver disease and are increasingly emerging as a global health problem. Such disorders can lead to liver damage, resulting in the release of pro-inflammatory cytokines and the activation of infiltrating immune cells. These are some of the common features of ALD progression in ASH (alcoholic steatohepatitis) and NAFLD to NASH (non-alcoholic steatohepatitis). Hepatic steatosis, followed by fibrosis, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 199 publications
(231 reference statements)
1
8
0
Order By: Relevance
“…In fact, a significant decrease in the levels of transaminases was observed, along with a reduction in the amount of total protein. These findings indicate that, similarly to other natural hepatoprotective natural compounds [27], the natural extract under investigation exerts protective effects on the functional and antioxidant liver enzymes, which is also supported by the performed histological analysis.…”
Section: Discussionsupporting
confidence: 77%
“…In fact, a significant decrease in the levels of transaminases was observed, along with a reduction in the amount of total protein. These findings indicate that, similarly to other natural hepatoprotective natural compounds [27], the natural extract under investigation exerts protective effects on the functional and antioxidant liver enzymes, which is also supported by the performed histological analysis.…”
Section: Discussionsupporting
confidence: 77%
“…The molecular machinations guiding curcumin's hepatoprotective impact also call for deeper, more detailed inquiries. While curcumin’s potency in managing diverse chronic conditions is documented, there's a pressing need for exhaustive studies within expansive and varied patient demographics to ascertain its efficacy in ALD treatment [121] .…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin is another compound with properties that can be used in cancer prevention, including HCC prevention, by counteracting hepatocyte damage, particularly in cases of exposure to toxic substances [ 80 , 81 ]. The substance mitigates inflammation and fibrosis in the liver [ 82 ]. A meta-analysis conducted by Paul Fernández-Palanca et al indicated that quercetin has antiproliferative and pro-apoptotic effects on HCC cells [ 83 ].…”
Section: Plant Hepatoprotective Compoundsmentioning
confidence: 99%
“…Its anti-cancer properties have been repeatedly proven [ 89 ]. In addition to its antioxidative and cell-protective effects, its particular property is preventing angiogenesis in the tumor and the entire liver area, preventing fibrosis [ 82 ]. This is possible through the inhibition of vascular endothelial growth factor secretion and activation of Nrf2 (nuclear factor erythroid 2-related factor 2), which acts protectively on cells [ 82 ].…”
Section: Plant Hepatoprotective Compoundsmentioning
confidence: 99%